Analyzing the Use of Fillers in Postgraduate EFL Learners' Academic Presentations: A Qualitative Case Study Approach - Gesha Fauziyyah; Andang Saehu; Cipto Wardoyo (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2026)
This study explores the use of fillers in academic presentations by EFL (English as a Foreign Language) learners, aiming to understand their functions and impact on communication during academic presentations. The research used a qualitative method that analyzed 373 fillers uttered by 3 students during their presentations, classifying them into simple words, phrases, and clauses. Data collection was conducted through audio and video recordings of the participants' presentations. The data was manually transcribed to form a corpus of the students’ spoken language. Common fillers like “Ehmm,” “okay,” “so,” and “I think” were identified. Some of their functions, such as signaling hesitation, providing thinking time, and clarifying points, were examined. The findings suggest that while fillers help maintain speech flow and engage the audience, using them too much can make the speaker seem less confident or unprepared. The study shows that fillers can be useful when used thoughtfully, but overusing them can affect the clarity and professionalism of the presentation. The research suggests that students could benefit from being more aware of how they use fillers, and instructors might include training on managing fillers in their presentation workshops. In terms of academic implications, this research highlights the need for further exploration into the cognitive and social functions of fillers in EFL contexts. Practical implications for EFL instructors include incorporating targeted exercises into speaking curricula, such as awareness-building activities, real-time feedback, and guided practice sessions, specifically focused on managing the use of fillers in academic settings.